Proceedings of the 10th Annual Conference on Genetic and Evolutionary Computation 2008
DOI: 10.1145/1389095.1389134
|View full text |Cite
|
Sign up to set email alerts
|

A multi-scaled approach to artificial life simulation with P systems and dissipative particle dynamics

Abstract: Compartmentalisation is thought to have been a crucial step in the origin of life. To help us bridge the gap between selfassembly processes behind the formation of bio-compartments and metabolic and information bearing processes we refer to DPD and P Systems Simulations. In this paper we outline a new software platform linking a high level abstract computational formalism (P Systems) with a molecular scale model (Dissipative Particle Dynamics) by linking the membranes which delimit the cellular regions within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Evaluation of the fluorescence as a function of time showed that the vesicle cargo was slowly released, indicating a measurable response to an external stimulus. These results can be compared with those from simulations presented in our previous work (Smaldon et al 2008), in which the diffusion rate of encapsulated particles within vesicles containing different numbers of membrane pores was determined in simulation. The results are presented in Fig.…”
Section: Potential Routes To a Chemical Implementationmentioning
confidence: 97%
See 1 more Smart Citation
“…Evaluation of the fluorescence as a function of time showed that the vesicle cargo was slowly released, indicating a measurable response to an external stimulus. These results can be compared with those from simulations presented in our previous work (Smaldon et al 2008), in which the diffusion rate of encapsulated particles within vesicles containing different numbers of membrane pores was determined in simulation. The results are presented in Fig.…”
Section: Potential Routes To a Chemical Implementationmentioning
confidence: 97%
“…In our previous work, a prototype version of the P systems and DPD based simulation and modelling framework was used to investigate the effect of poration on the rate of diffusion of encapsulants through vesicle membranes (Smaldon et al 2008). The results from simulation indicated a linear relationship between the number of pores present in the membrane and the rate of diffusion.…”
Section: Potential Routes To a Chemical Implementationmentioning
confidence: 99%
“…At the core of these entities are gene transcriptional systems encapsulated within self-assembled vesicles (in this case liposomes), spherical membranes which provide a selectively permeable barrier around a surrounded volume of fluid. This approach is similar in some aspects to membrane computing [18], in which computation can take place by applying reaction rules to chemicals within encapsulated volumes, and in [23] we employed a hybrid DPD-membrane computing technique to simulate diffusion in vesicles. In contrast with the most common, top-down, approach to synthetic biologic, we advocate a bottom-up approach with engineered components of manageable complexity.…”
Section: Introductionmentioning
confidence: 99%